PKCε activator protects hippocampal microvascular disruption and memory defect in 3×Tg-Alzheimer’s disease mice with cerebral microinfarcts - Wang, Huaixing; Zhang, Zongxiu; Hongpaisan, Jarin (Frontiers in Aging Neuroscience, 2023)
Background Current evidence suggests that microvessel disease is involved in Alzheimer’s disease (AD). Cerebrovascular disease correlates with cardiovascular disease and is complicated in ≈40% of AD patients. The protein kinase C (PKC) ε activator DCPLA can stimulate human antigen (Hu) R that prevents degradation and promotes the translation of mitochondrial Mn-superoxide dismutase (MnSOD) and vascular endothelial growth factor-A (VEGF) mRNAs. Methods To induce brain microinfarcts, we injected triple transgenic (3×Tg) and wild-type (WT) control mice with microbeads (20 μm caliber) into common carotid arteries, with or without the DCPLA-ME (methyl-ester) for 2 weeks. After water maze training, mice at 16 months old were examined for confocal immunohistochemistry at a single cell or microvessel level in the hippocampal CA1 area, important for spatial memory storage, and in the dorsal hippocampus by western blots. Results In 3×Tg mice without cerebral microinfarcts, an accelerating age-related increase in (mild) oxidative stress and hypoxia inducible factor (HIF)-1α, but a reduction in VEGF, mitochondrial transcription factor A (TFAM), and MnSOD were associated with capillary loss. The change was less pronounced in arterioles. However, in 3×Tg mice with cerebral microinfarcts, increasing arteriolar diameter and their wall cells were related with the strong oxidative DNA damage 8-hydroxy-2′-deoxyguanosine (8-OHdG), apoptosis (cleaved caspase 3), and sustained hypoxia (increased HIF-1α and VEGF/PKCε/extracellular signal regulated kinase or ERK pathway). Microocclusion enhanced the loss of the synaptic marker spinophilin, astrocytic number, and astrocyte-vascular coupling areas and demyelination of axons. DCPLA-ME prevented spatial memory defect; strong oxidative stress-related apoptosis; sustained hypoxia (by reducing HIF-1α and VEGF); and exaggerated cell repair in arteriolar walls, pericapillary space dilation, neuro-glial-vascular disruption, and demyelination. Conclusion In conclusion, in 3×Tg mice with cerebral microinfarcts, sustained hypoxia (increased HIF-1α and VEGF signals) is dominant with arteriolar wall thickening, and DCPLA has a protective effect on sustained hypoxia.